Synthesis and characterization of phenolic resins based on pyrolysis bio-oil separated by fractional condensation and water extraction. (April 2022) - Xu, J.; Brodu, N.; Mignot, M.; Youssef, B.; Taouk, B.
Abstract: The combination of fractional condensation and water extraction methods is proposed to produce phenol rich beech wood pyrolysis bio-oil fractions, which have great potential to replace petroleum-based phenol in polymerization of novolac resin. The polymerization of model phenol acetaldehyde (MPA) resins, mimic acetaldehyde (mimic) resin which base on the composition of phenol compounds in bio-oil, and bio-oil acetaldehyde (BOA) resins were studied. MPA and mimic resins were used to compare with the BOA resins to determine the feasibility of using bio-oil. Bisphenol A type epoxy resin (DGEBA) was used, for the first time, as a formaldehyde-free cross-linker for bio-oil based novolac resins. The kinetic parameters of the curing reaction with model-free methods were obtained using data from a differential scanning calorimeter (DSC). The BOA resin showed curing activation energy was close to that of the phenol-acetaldehyde (PA) resin (95.5 and 94.9 kJ/mol by Kissinger method). The physicochemical and thermal properties of the novolac resins before and after curing are compared, and the potential of treated bio-oil products to effectively replace commercial phenols is demonstrated. Highlights: Bio-oil fractions obtained by condensation were used to prepare novolac resin Water insoluble bio-oil fraction has a potential to replace phenol A formaldehyde-free cross-linker was used for bio-oil based novolac resins The curing kinetic parameters were studied using differential calorimetry A lower curing initial temperature was obtained using bio-oil resin